The Effect of Implementing the School Activity Plan and Budget Application (Arkas) and Its Impact on the Accountability and Transparency of Bos Funds (Case Study of SMK in Bandar Lampung City) - Soimah, Soimah; Darmawan, Jaka (Prosiding International conference on Information Technology and Business (ICITB), 2023)
This study aims to determine (1) the effect of using the school budget work plan application (ARKAS) on accountability for the use of BOS funds in Vocational High Schools in Bandar Lampung City, (2) the effect of using the school budget work plan application (ARKAS) on the transparency of the use of BOS funds in Vocational High Schools in Bandar Lampung City. The type of research used in this study is quantitative descriptive research. The population in this study is all Private Vocational High Schools receiving BOS Phase I in 2022 in Bandar Lampung City. The sampling technique is purposive sampling, selecting as many as 30 school treasurers. Data collection techniques are questionnaires and documentation. Data analysis techniques use descriptive analysis in the form of percentages and inferential analysis using analysis prerequisite testing, hypothesis testing, and determination coefficient tests. The results showed that: (1) there is an effect of the use of the school budget work plan application (ARKAS) on the accountability of the use of BOS funds in Vocational High Schools in Bandar Lampung City, where the better the use of the ARKAS application, the more accountable the use of BOS funds, (2) there is a significant influence on the use of the school budget work plan application (ARKAS) on the transparency of the use of BOS funds in Vocational High Schools in Bandar Lampung City.Key words: Use of the School Budget Work Plan Application (ARKAS), accountability for the use of BOS funds, transparency in the use of BOS funds